Gold nanoparticle-coated capillaries for protein and peptide analysis on open-tubular capillary electrochromatography - Hamer, Mariana (2012)
We report a new method of immobilization of gold nanoparticles (AuNPs) on a fused-silica capillary through covalent binding. The resulting modified capillary was applied to electrophoretic systems to improve the efficiency of separation and the selectivity of selected solutes. The immobilization of AuNPs on the capillary wall was performed in a very simple and fast way without requiring heating. The surface features of an AuNP-coated capillary column were determined using the scanning electron microscopy. The chromatographic properties of AuNP-coated capillaries were investigated through variation of the buffer pH and separation voltage. Effective separations of synthetic peptides mixture were obtained on the AuNP-coated capillaries. The method shows a remarkable stability since it was reused about 900 times. The capacity factor was duplicated. Therefore, this modification is stable and can be applied to different separation purposes. A complex mixture of tryptic peptide fragments of HSA was analyzed in both the bare- and the AuNP-coated capillaries. Better electrophoretic peptide profile was observed when using the AuNP-coated capillary.